Cudowność i baśniowość w powieści Deotymy Branki w jasyrze - Woszczak, Izabela (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article centres around the problems connected with wonders, miracles and fairy tale themes in Branki w Jasyrze, a nineteenth century novel written by Jadwiga Łuszczewska (pen name. Deotyma). This paper begins with biographical information about Deotyma‘s family life, upbringing and its influence on her future career; reception of her charismatic personality and writing; and finally about her attitude to the employment of fantasy motives in literature. The main aim of this article is to investigate different types of miraculous events that take place in Branki w Jasyrze. Those phenomena derive from various cultural and artistic frameworks: medieval hagiography, traditional folk fairy tale and primitive beliefs connected with Mongolian shamanism. In fact, this diversity has its purpose: Łuszczewska gathered all kinds of wonders to reveal the unity of people’s transcendental apprehensions.